Improving Students’ Writing Skill Through The Implementation of Animated Short Movie in Teaching Writing Narrative Text - W.A. Pangestu; P.A. Adiwijaya; N.M.A. Purnami (Universitas Pendidikan Ganesha, 2021)
This study aimed at proving that there was a significant improvement in the achievement of students' narrative text writing skills after being taught using animated short movie. This research was applied to the 10th grade students at SMK Praja Pandawa. This research is a classroom action research. In this study, the results of the data were processed using test measurements. The results of this study indicated that there was a significant improvement in students' writing skills from pre-test to post-test after being taught with animated short movie. The mean score of students before the test was 53.48, with a classical completeness percentage of 22.22% with a minimum KKM score of 60. Meanwhile, after the Post test 1 was carried out it became 61.33 with a classical completeness percentage of 59.26 and the mean score of students obtained after post test 2 was 80.59 with a classical completeness percentage of 100%. These results proved that the researcher's treatment had a positive impact on the achievement of students' final results so it can be concluded that the application of animated short movie in the classroom could improve the achievement of writing skills of 10th grade students of SMK Praja Pandawa.